Inflight radiometric calibration of New Horizons’ Multispectral Visible Imaging Camera (MVIC) - Howett, CJA; Parker, AH; Olkin, CB; Reuter, DC; Ennico, K; Grundy, WM; Graps, AL; Harrison, KP; Throop, HB; Buie, MW; Lovering, JR; Porter, SB; et al. (Elsevier, 2016)
We discuss two semi-independent calibration techniques used to determine the inflight radiometric calibration for the New Horizons’ Multi-spectral Visible Imaging Camera (MVIC). The first calibration technique compares the measured number of counts (DN) observed from a number of well calibrated stars to those predicted using the component-level calibration. The ratio of these values provides a multiplicative factor that allows a conversation between the preflight calibration to the more accurate inflight one, for each detector. The second calibration technique is a channel-wise relative radiometric calibration for MVIC's blue, near-infrared and methane color channels using Hubble and New Horizons observations of Charon and scaling from the red channel stellar calibration. Both calibration techniques produce very similar results (better than 7% agreement), providing strong validation for the techniques used. Since the stellar calibration described here can be performed without a color target in the field of view and covers all of MVIC's detectors, this calibration was used to provide the radiometric keyword values delivered by the New Horizons project to the Planetary Data System (PDS). These keyword values allow each observation to be converted from counts to physical units; a description of how these keyword values were generated is included. Finally, mitigation techniques adopted for the gain drift observed in the near-infrared detector and one of the panchromatic framing cameras are also discussed.